Inbreeding and Genetic Trend of Dairy Cattle in Baturraden Dairy Cattle Breeding Centre: A Short Communication - Susanto, A; Santosa, SA; Sudewo, ATA (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2010)
The success (or failure) of a breeding centre can be assessed through the genetic trend of trait(s) included in the breeding objective and the inbreeding trend. Through continuous genetic evaluation and structured mating program, positive genetic trend while maintaining inbreeding on the reasonable level will be achieved. Inbreeding level of a population is an important aspect in animal breeding as this may lead to a deteriorating phenomenon called inbreeding depression. This information will guide the animal breeder on how the mating system of their animals will be designed. Inbreeding level of a dairy cow population generally is maintained to be less than 10%. The trend of additive genetic (breeding value) and inbreeding of dairy cattle population in Baturraden Dairy Cattle Breeding Centre (Balai Besar Pembibitan Ternak Unggul Sapi Perah, BBPTU) was examined. The pedigree data consisted of 450 animals and 861 records were analyzed. The study included two traits namely milk yield (MY) and calving interval (CI). The pedigree data were collected from 1977 to 1990. The breeding value (EBV) of animals was estimated using DMU computer package applying repeatability animal model and the coefficient of inbreeding was computed with SECATEURS. The study showed zero inbreeding level of the population based on the pedigree available without any single inbred animal. The population showed no genetic progress over years during the period of 1977-1990 based on linear regression of EBVs on the year of birth. This indicated that during the period of 1977 and 1990 the genetic improvement program in BBPTU was unsuccessful. The inbreeding level of zero could mean that the designed mating system was successful. However, no genetic progress and no inbreeding trend could mean that no selection program has been introduced in the breeding centre. (Animal Production 12(3): 144-149 (2010)Key Words: genetic trend, inbreeding trend, BBPTU Baturraden, dairy cattle